The phoenix of the memory - Serra, Luis Esteve Casellas; Olivera, Luis M. Hernández (Tábula, 2019)
If we google the word archivo (archive or file in English) the first result will be the definition of computer file by Wikipedia: “a computer file is a set of bits that are stored on a device.” In English, archive directly shows the URL of the Internet Archive, which according to the sameWikipedia, is “a nonprofit digital library dedicated to the preservation of archives, captures from public Web sites, multimedia resources and also software.” The impact of these results and their perception by users is proportional to the importance of the linking tools in the retrieval and presentation of information: Google, the web with more hits in the world, and Wikipedia, the more consulted information web, with thousands of queries per second everyday.